IMPLEMENTASI PROGRAM KERJASAMA THAILAND DI BIDANG PARIWISATA MELALUI INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE (IMT-GT) TAHUN 2017-2021 - Salsabila Abadi Putri; Megahnanda Alidyan Kresnawati (Halu Oleo University, 2023)
The purpose of this study was to find out Thailand's implementation of IMT-GT subregional cooperation in increasing tourism in the 2017-2021 period. The cooperation between the three countries, known as the Growth Triangle, is a transnational economic zone intertwined with adjacent geographical areas. The research method uses a qualitative descriptive approach, with the scope of this research starting from 2017 to 2021, according to the time period of the IMT-GT Implementation Blueprint. This research is descriptive in nature and is of a qualitative type using literature study data collection techniques or collecting data appropriate to the research topic, such as online journals, online reports, such as the official Thai tourism website, the official IMT-GT website, ASEAN, global media news, Thailand, Malaysia, and Indonesia. The results of this study indicate that based on the regional strategic plan focusing on the tourism sector in the implementation of the IMT-GT blueprint, Thailand's policy implementation is divided into two focuses, namely building infrastructure consisting of building tourist attractions and building transportation facilities which aim to increase connectivity between IMT-GT sub-regions, as well as the Thai government's tourism promotion or marketing to increase international tourist arrivals, both globally, and from IMT-GT countries.